Tax Deductibility of Commuting Expenses and Residential Land Use with more than one Center - Matthias Wrede (Center for Economic Studies and ifo Institute (CESifo), 2003)
This paper analyzes the treatment of commuting expenses by the income tax code from a normative and a positive point of view within a continuous space framework with endogenous residence choices and perfect labor mobility. As commuting expenses should never be deductible from the income tax base in a first-best world, deductibility might well be the outcome of a second-best-optimum-tax approach provided that not all factors of production were mobile. Non-deductibility might be justified by a lack of instruments to internalize environmental and congestion externalities or by perfect mobility of all production factors. However, the existence of deductions in many coun-tries can be easily explained within a public choice framework by redistribution from non-commuters to commuters.
Keywords: H21; J61; R13; 330; Income tax; relief; residential land use; labor mobility; commuting expenses; optimum taxation